2008
DOI: 10.1007/s00249-008-0319-7
|View full text |Cite
|
Sign up to set email alerts
|

The voltage dependence of hEag currents is not determined solely by membrane-spanning domains

Abstract: The ether-à-go-go potassium channels hEag1 and hEag2 are highly homologous. Even though both possess identical voltage-sensing domain S4, the channels act differently in response to voltage. Therefore we asked whether transmembrane domains other than the voltage sensor could contribute to the voltage-dependent behaviour of these potassium channels. For this chimaeras were created, in which each single transmembrane domain of hEag1 was replaced by the corresponding segment of hEag2. The voltage-dependent proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Despite the presence of about 70% identity in amino acid sequence between the Eag1 and Eag2 K + channel proteins [4,6], the structural bases of their different voltage-gating properties and subcellular localizations have remained largely elusive. Previous biophysical analysis of a series of different chimeras between human Eag1 and Eag2, for example, revealed that the transmembrane regions alone were not sufficient to explain the differences in their gating kinetics and steady-state voltage-dependence [25,26]. In addition, similar to our results here (Figure 8), non-membrane regions per se were found not to determine their gating behaviors [26].…”
Section: Discussionsupporting
confidence: 74%
“…Despite the presence of about 70% identity in amino acid sequence between the Eag1 and Eag2 K + channel proteins [4,6], the structural bases of their different voltage-gating properties and subcellular localizations have remained largely elusive. Previous biophysical analysis of a series of different chimeras between human Eag1 and Eag2, for example, revealed that the transmembrane regions alone were not sufficient to explain the differences in their gating kinetics and steady-state voltage-dependence [25,26]. In addition, similar to our results here (Figure 8), non-membrane regions per se were found not to determine their gating behaviors [26].…”
Section: Discussionsupporting
confidence: 74%
“…The voltage dependence of both constructs was almost identical with a slope of 26.23±4.24 mV for K V 10.1 and 25.63±1.76 mV for K V 10.1-BBS. Also, both constructs displayed rectification at very positive potentials [45].…”
Section: Resultsmentioning
confidence: 93%
“…We performed two-electrode voltage-clamp recordings to measure current-voltage relationships and channel activation kinetics as described previously [45].…”
Section: Methodsmentioning
confidence: 99%
“…It is reasonable to assume, however, that the cytoplasmic domains of both channels are functionally similar, since a chimeric channel carrying the PAS domain, C-linker, and CNBHD of HERG on an Eag1 background results in behavior not massively different from wild type Eag1. 28 The mature Eag1 is core glycosylated on Asn-388 and complex glycosylated on Asn-406. Proper glycosylation is required for efficient transport to the plasma membrane, but also enzymatic removal of glycosylation causes a large reduction of the peak current, indicating that the presence of sugar moieties impacts the functional properties of Eag1 channels at the plasma membrane.…”
Section: Structurementioning
confidence: 99%